The Moderating Role of Transformational Leadership in Managing Turnover Intention Among Generation Z Employees in Surabaya - Bernardus Aris Ferdinan (AIBPM Publisher, 2025)
This study aims to examine turnover intention among Generation Z employees in Surabaya, Indonesia. The sample consisted of 212 non-managerial employees. Data were collected through an online survey using Google Forms and analyzed using Structural Equation Modeling (SEM) via SmartPLS software. The results revealed that workplace incivility has a positive and significant effect on burnout; workplace incivility also has a positive and significant effect on turnover intention; burnout positively and significantly influences turnover intention; burnout mediates the relationship between workplace incivility and turnover intention; and transformational leadership moderates the relationship between workplace incivility and burnout.The practical implication of this study emphasizes the importance of leadership in fostering a positive communication culture, building rapport among employees, being proactive in conflict resolution, and taking firm action against inappropriate workplace behavior. Theoretically, the findings contribute to a deeper empirical understanding of the moderating role of transformational leadership. Leadership has been shown to act as a psychological buffer but may not entirely resolve psychological distress experienced by employees.